Love after all - Burton, Jaci (Burton, Jaci. Hope novels., 2015)
High school math teacher Chelsea Gardner, tired of dating the wrong men, has developed a foolproof list to help her find her soulmate, but bar owner Sebastian Palmer tries to convince her that she is going about things all wrong.